(untitled) (Bangladesh Journal of Urology, 2020)
A 28 years old male with well developed secondary sexual characteristics was admitted in BSMMU with a grossly swollen, malformed phallus and passage of urine mostly through an opening in the perineum. After birth, his parents noticed that when the baby micturates the phallus is swollen and few drops of urine comes out through the external urethral meatus but most of the urine comes out through an opening in the perineum. No treatment was taken by his parents for this complaint. At puberty his secondary sexual characteristics developed normally. He felt sexual urge towards females but his penis was not erected. At the peak of his sexual excitement, orgasm occurs with release of whitish seminal fluid which comes mostly through perineal opening. His general physical examination was unremarkable & examination of the genitalia revealed well developed scrotum. Both of the testes were normal in size, shape and consistency but the penile shaft was large and flabby, and the ventral aspect of the penis appeared as a sac with mild pseudo phimosis. Careful palpation suggested the absence of the corpus spongiosum & corpora cavernosa. Both these findings were subsequently confirmed by a duplex colour doppler study. The penis distended ventrally when he tried to micturate and the urinary stream was narrow. About 75% of urine flow evacuates through perineal opening which was located about 2 cm from anal opening in the midline ventrally. A voiding cystourethrogram revealed that whole of the anterior urethra was grossly dilated with narrowing at the bulbar part & external urerthral meatus. There was another passage (about 5 cm) from the scrotal margin up to proximal posterior urethra. Cystogram showed a bladder diverticulum at left lateral wall. An urethrocystoscopic examination revealed that just proximal to the stenosed external urethral meatus the urethra is widely dilated which seemed like a transparent fusiform sac with irrigating fluid. Whole of the anterior urethra was very thin walled with transmitting lights through it. Proximal part of the urethra near the external sphincter was grossly narrowed. Urethrocystoscope was also introduced through the abnormal urethral opening into the perineum which was located in the midline raphe of the perineal region about 2 cm from the anal verge. This urethra joined with the penile urethra distal to the external sphincter. Prostatic part of the common urethral channel was normal containing verrumontanum and a normal bladder neck. Bangladesh Journal of Urology, Vol. 19, No. 1, Jan 2016 p.53-56